Extraintestinal Manifestations in Vedolizumab and Anti-TNF-Treated Patients With Inflammatory Bowel Disease. Issue 9 (13th April 2018) - Dubinsky, Marla C; Cross, Raymond K; Sandborn, William J; Long, Millie; Song, Xue; Shi, Nianwen; Ding, Yao; Eichner, Samantha; Pappalardo, Brandee; Ganguli, Arijit; Wang, Anthony
Abstract: Background: Extra-intestinal manifestations (EIMs) can impact morbidity in patients with inflammatory bowel diseases (IBD; Crohn's disease [CD] and ulcerative colitis [UC]). This study compared incidence rates of EIMs in patients with moderate to severe IBD receiving gut-selective vedolizumab (VDZ) vs those receiving systemic anti–tumor necrosis factor (anti-TNF) therapies. Methods: Adult IBD patients receiving VDZ or anti-TNFs were identified from the MarketScan claims database from September 28, 2012, through September 30, 2016. Incidence rates of EIMs were compared between the 2 cohorts. Descriptive analyses were performed for all courses of treatment. Generalized linear models estimated the impact of treatment on the likelihood of developing EIMs. Results: Compared with patients receiving anti-TNF therapy, VDZ-treated CD patients were 28% more likely to develop "any EIMs" (adjusted incident rate ratio [IRR], 1.28; 95% confidence interval [CI], 1.02–1.62). Specifically, CD patients treated with VDZ were more likely to develop erythema nodosum (IRR, 4.29; 95% CI, 1.73–10.64), aphthous stomatitis (IRR, 3.73; 95% CI, 1.51–9.23), episcleritis/scleritis (IRR, 2.51; 95% CI, 1.02–6.14), arthropathy (IRR, 1.45; 95% CI, 1.15–1.84), primary sclerosing cholangitis (PSC) (IRR, 7.79; 95% CI, 3.32–18.27), and uveitis/iritis (IRR, 2.89; 95% CI, 1.35–6.18). UC patients receiving VDZ did not have a statistically significant increase in "any EIMs" vs patients receiving anti-TNFs, but were more likely to develop specific EIMs (aphthous stomatitis: IRR, 3.67; 95% CI, 1.30–10.34; pyoderma gangrenosum: IRR, 4.42; 95% CI, 1.00–19.45; and PSC: IRR, 3.44; 95% CI, 1.23–9.68). Conclusions: IBD patients receiving VDZ may be more likely to develop EIMs vs patients receiving anti-TNF therapies. The gut-selective inflammatory control of VDZ may potentially limit its clinical effect on EIM prevention.